THE INTERPLAY OF SOCIAL AND PHYSICAL CAPITAL AS RESOURCES IN RURAL COMMUNITIES: IMPLICATIONS FOR STUDENTS’ PERCEPTIONS AND ACADEMIC PERFORMANCE: Received: 11th November 2025, Revised: 21st November 2025, 25th November 2025, Accepted: 27st November 2025, Date of Publication: 28th November 2025 - Wisanu Krutngoen (PEOPLE: International Journal of Social Sciences, 2025)
This study examines the interplay between social and physical capital resources in shaping students’ perceptions, motivation, and academic performance across two rural community contexts—L County (high-performing) and F County (low-performing), Kentucky. The primary objective is to explore how community-level resources influence students’ educational orientations and how these dynamics vary between high- and low-achieving groups. Grounded in motivation theory and cultural models theory (D’Andrade & Strauss, 1992; Gee, 1996), the study conceptualizes social and physical capital as motivational structures that mediate students’ agency, aspiration, and achievement. Employing a pragmatic mixed-methods design, the research integrates quantitative analysis (n = 42) with qualitative interviews (n = 40). Quantitative findings indicate that in L County, students’ motivation was primarily shaped by teacher influence (r = 0.596, p < .01), whereas in F County, motivational drivers were dispersed across teachers, peers, and parents, reflecting weaker coherence. Qualitative evidence further reveals that deficits in physical capital—such as inadequate infrastructure, limited facilities, and restricted local opportunities—indirectly constrained long-term aspirations, while social capital, particularly through teacher and family relationships, exerted a more immediate influence on motivation and performance. Overall, the findings suggest that the quality and coherence of social relationships, rather than the quantity of available resources, are decisive factors in educational success. The study contributes to the sociology of education by integrating spatial and relational dimensions of capital into motivational analysis and by illuminating how students in resource-constrained settings mobilize social and physical capital to navigate structural inequalities and pursue academic advancement.